2013
DOI: 10.1111/jcmm.12056
|View full text |Cite
|
Sign up to set email alerts
|

Formation of functional gap junctions in amniotic fluid‐derived stem cells induced by transmembrane co‐culture with neonatal rat cardiomyocytes

Abstract: Amniotic fluid-derived stem cells (AFSC) have been reported to differentiate into cardiomyocyte-like cells and form gap junctions when directly mixed and cultured with neonatal rat ventricular myocytes (NRVM). This study investigated whether or not culture of AFSC on the opposite side of a Transwell membrane from NRVM, allowing for contact and communication without confounding factors such as cell fusion, could direct cardiac differentiation and enhance gap junction formation. Results were compared to shared m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Additionally, previous studies found that more than 90% of pluripotent cells will express Nkx-2.5 and Islet-1 at day 8 of the differentiation Following the attempted differentiation protocol, connexin 43 preferentially located to the cell membranes between cells. This occurrence has been observed following other cardiac differentiation attempts in AFSC [9][10][11]. Connexin 43, also known as gap junction alpha-1 protein, is a dominant connexin expressed in cardiovascular tissue and is a key component to gap junctions [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, previous studies found that more than 90% of pluripotent cells will express Nkx-2.5 and Islet-1 at day 8 of the differentiation Following the attempted differentiation protocol, connexin 43 preferentially located to the cell membranes between cells. This occurrence has been observed following other cardiac differentiation attempts in AFSC [9][10][11]. Connexin 43, also known as gap junction alpha-1 protein, is a dominant connexin expressed in cardiovascular tissue and is a key component to gap junctions [28].…”
Section: Discussionmentioning
confidence: 99%
“…Upon direct co-culture of AFSC with neonatal rat ventricular myocytes (NRVM), human cells positive for cardiac markers such as sarcomeric proteins have been observed [8][9][10]. However, when AFSC are co-cultured with NRVM in systems that do not allow for cell fusion, including on opposite sides of a porous membrane, in shared media dishes, and AFSC in conditioned medium from NRVM, it is observed that AFSC form functional gap junctions but do not express sarcomere proteins [11]. It has also been observed that treatment of AFSC with the demethylating agent 5-aza-2'-deoxycytidine for 24 hours at the beginning of a 10 day culture period results in phenotypic changes of the cells consistent with muscle cells and protein expression of cardiac troponin I (cTnI) and cardiac troponin T (cTNT), but no mature sarcomeres or spontaneous contraction [9].…”
Section: Introductionmentioning
confidence: 99%
“…[22,39] The experimental protocol and informed consent forms were approved by the Institutional Review Boards of Baylor College of Medicine and Rice University.…”
Section: Isolation Of Human Afscmentioning
confidence: 99%
“…Human MSCs can make cardiac connexins (Cx43, Cx 40 and Cx 45) and form gap junctional complex. It is recently reported that amniotic fluid-derived stem cells differentiate into cardiomyocyte-like cells and form gap junctions when directly mixed and cultured with neonatal rat ventricular myocytes [50]. Similar to other cells, toxic agents also affect viability, morphology, and function of MSCs.…”
Section: Fig 7: Different Physical Chemical or Biological Agents Amentioning
confidence: 99%